PEMBELAJARAN BIOLOGI BERBASIS KEARIFAN LOKAL DALAM UPAYA PELESTARIAN KEANEKARAGAMAN SUMBER DAYA HAYATI - I Made Subrata; I Wayan Suanda; I Gusti Ayu Rai (Widyadari, 2025)
Local wisdom (local knowledge, local wisdom) acts as a source of innovation and skills that can be empowered for the welfare of society. Local wisdom related to natural resources, especially the diversity of biological resources, culture and customs contains a moral message that society always maintains natural resources and traditional traditions so that they do not change due to the development of the times. Biology, which discusses living things, including their variety, origins, habitat, interactions, utilization and sustainability, has been philosophically reflected in the social order of life in the form of local wisdom. The purpose of writing this article is to reveal that local wisdom can be used as a medium for learning biology in schools, and can also be used as a learning resource so that students are motivated to improve their scientific literacy skills in studying local wisdom into biology learning materials, so that its existence can be preserved. Local wisdom-based learning in the future is expected to instill character in the community to maintain and preserve ancestral heritage, especially biological resources, to be used sustainably to support community life. This writing method uses a literature review method combined with direct experience in society. The implementation of local wisdom-based learning can be in the form of assigning students to write papers and integrate them into biology learning materials about several local wisdoms of the Balinese people that have existed for generations in the form of religious ceremonies, mythology, and advice that is highly adhered to by the community.